دور الإبداع والإبتكار في تعزيز الميزة التنافسية للمؤسسات الجزائرية - حميدى، عبدالرزاق; بن عنتر، عبدالرحمان Bin Antar, Abdulrahman (المدرسة العليا للتجارة - مخبر الإصلاحات الإقتصادية، التنمية واستراتيجيات الإندماج في الإقتصاد العالمي, 2021)
يشهد العالم المعاصر تغيرات وتطورات متلاحقة تعود لأسباب اقتصادية وثقافية وسياسية وتكنولوجية، وتتجلى في مظاهر عدة، كالعولمة واشتداد حدة التنافس والانفجار الرقمي والمعرفي، وإزاحة القيود بين الدول، كل هذه العوامل شكلت الدافع الأساسي لنشوء اقتصادي قائم على الابتكار والإبداع والمعرفة. وعلى اعتبار ان الازدهار والرقي الذي تعرفه الدول المتقدمة لم يكن إلا نتاجا لما تعرفه من اهتمام وتشجيع للإبداع والابتكار والأفكار الخلاقة، فإن الجزائر باتت مجبرة على الاهتمام بهذا المجال وإيلائه الأهمية اللازمة. وفي هذا الصدد تبذل الجزائر جهودا حثيثة لتطوير المؤسسات الاقتصادية وتعزيز دورها في النهوض بالاقتصاد الوطني وتنمية الصادرات خارج قطاع المحروقات، ومما لا شك فيه إن الإبداع والابتكار يعد أحد المداخل المهمة لتطوير المؤسسات الجزائرية وتعزيز تنافسيتها. من هنا تهدف دراستنا إلى توضيح دور الإبداع والابتكار ومدى أهميته للمؤسسات الاقتصادية الجزائرية، حيث أصبح هذا الأخير يحضى بأهمية بالغة، خاصة في ظل التنافس الحاد بين المؤسسات التي تسعى إلى تفعيل دور الإبداع والابتكار في تعزيز ميزتها التنافسية.
The contemporary world is witnessing successive changes and developments due to economic, cultural, political and technological reasons, which are manifested in several aspects, such as globalization, intensifying competition, digital and cognitive explosion, and the remove of barriers between countries. These factors represent the primary motivation for an economic development based on innovation, creativity and knowledge. Considering that the prosperity and progress of the developed countries is a result of the encouragement of creativity, innovation and creative ideas, Algeria should pay attention to this field and give it the necessary importance, especially with the dependence on oil (60% of its budget and nearly 90% of its exports). In this regard, the Algerian authorities makes vigorous efforts to develop the economic institutions and enhance its role in the promotion of the national economy and developing exports outside the oil's sector. Creativity and innovation are undoubtedly an important entry point for the development and competitiveness of Algerian enterprises. This study aims to clarify the role of creativity and innovation and its importance to the Algerian economic institutions, especially in light of the intense competition between the institutions which are trying to activate the role of creativity and innovation in enhancing its competitive advantage.
Keywords: الإبداع الإداري -- الميزة التنافسية -- التميز المؤسسي -- منظمات الأعمال -- الجزائر